The Future of Nigeria's Lithium Resources: Industrial Applications and Prospects – A Review (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Nigeria is home to significant lithium resources, particularly in regions such as Nasarawa, Kaduna, Oyo, Kwara, Kogi, Ekiti, and Plateau. These lithium-bearing pegmatites, mainly consisting of spodumene and lepidolite, contain high-grade lithium oxide (Li₂O) concentrations that are in demand globally due to the crucial role lithium plays in the development of clean energy technologies. As the world transitions away from fossil fuels, lithium is at the forefront of this shift, particularly in applications such as electric vehicle (EV) batteries, renewable energy storage systems, and consumer electronics. With the global market for lithium growing at an unprecedented rate, Nigeria stands poised to become a key player in the global lithium supply chain. However, while Nigeria’s lithium resources have the potential to bring significant economic benefits, the country’s lithium industry faces multiple challenges. Illegal mining practices, particularly in regions like Nasarawa’s Wamba community, have resulted in environmental degradation and human rights violations, including child labor. Additionally, foreign involvement in illegal mining activities, especially from countries such as China, complicates efforts to regulate the sector. Despite these challenges, there are substantial opportunities for growth and development in Nigeria’s lithium industry. To fully realize the economic potential of its lithium resources, Nigeria must focus on several key areas: the establishment of robust regulatory frameworks, the adoption of sustainable mining technologies, the development of critical infrastructure, and the promotion of public-private partnerships. With the right policies and investments, Nigeria can become a leading supplier of lithium for global clean energy technologies. This paper provides an overview of Nigeria’s lithium resources, exploring the current state of the industry, challenges faced, and strategies for leveraging these resources to contribute to the global clean energy transition while ensuring the country’s long-term economic growth and environmental sustainability.